Pengaruh Augmented Reality Terhadap Pemahaman Konsep Matematika - Syamsir; Nasruddin (Perhimpunan Ahli Teknologi Informasi dan Komunikasi Indonesia, 2024)
Enhancing pupils' comprehension of mathematical concepts is a significant difficulty in education, especially for abstract notions. This study seeks to examine the impact of Augmented Reality (AR) utilization on students' comprehension of mathematical topics. The research encompassed 60 students as participants, employing a quantitative methodology and a quasi-experimental framework. Data were obtained using learning interest questionnaires and kids' report card grades. The results of the regression analysis yielded the equation Y = 11.18 + 1.061X, demonstrating that augmented reality usage significantly enhances students' comprehension of mathematical topics. The constant a = 11.18 signifies the baseline level of comprehension, whereas the regression coefficient b = 1.061 denotes that each one-unit increment in AR utilization improves students' understanding by 1.061 units. Consequently, augmented reality utilization can function as an efficacious method to assist pupils in comprehending mathematical topics in a more dynamic and engaging manner. This paper advocates for the incorporation of augmented reality into mathematics education within schools